International and regional measures against Somali piracy: genuine but misguided - Badran, Essam Mahmoud (AUC Knowledge Fountain, 2010)
The increasing piracy in the Gulf of Aden has captured the attention of the international community. Somali pirates have proven their ability to attack all types of vessels from small yachts to giant oil supertankers. As a result, series of serious efforts by international community have been undertaken to put an end to this emerging phenomenon. These include, deploying the biggest anti-piracy fleet in modern history, permitting warships to purse pirates in Somali territorial waters under special conditions, and the new approach toward establishing international tribunals to prosecute pirates. However, there is a growing need to re-examine Somali piracy counter-measures and evaluate their effectiveness. In this respect, a profound analysis of the circumstances surrounding Somali piracy is required. It is crucial to question to what extent the current anti-piracy efforts respond to the original roots of the problem and the needs of Somalia. This research critically analyzes anti-piracy efforts taken by the international community and its impact on the ground. In this regard, a holistic approach was taken to examine Somali piracy. Any anti-piracy measures have to respond to the roots of the problem in order to guarantee their effectiveness in the long-term. Undoubtedly, building a military coalition to patrol ships passing through Somali waters is a needed measure to deter pirates. However, it is crucial to ask ourselves to what extent such measures are sustainable and to what extent it responds to the roots of the problem. Thus, the international community needs to look to the bigger picture and to carefully analyze factors contributing to spread of piracy especially off the coast of Somali. The solution to piracy may lie on the land not in the sea.